A handheld confocal microendoscope compatible with laparoscopy for histology in situ. (May 2023) - Lu, Tingting; Li, Hua; Zhang, Wenyi; Deng, Yong; Liu, Qian; Fu, Ling
Highlights: The effects of NA and FOV on fluorescence collection efficiency were explored through Monte Carlo simulations. This provided theoretical guidance for the determination of the objective lens design parameters. A handheld probe with high NA, large FOV and cellular resolution was designed and fabricated to provide cellular structure information in real time. Ex vivo/in situ tissue imaging results of multiple organs in SD rats show the performance of the handheld large FOV rigid CM system with a half-millimeter diameter FOV, cellular resolution, and real-time imaging. Abstract: Large-area in situ real-time imaging with cellular resolution is important in small animal imaging and clinical diagnoses. Laparoscopy is a commonly used technical tool in minimally invasive surgeries. However, laparoscopies cannot achieve cellular resolution. Here we propose a handheld rigid confocal microendoscope with a high numerical aperture, large imaging field of view, and high-resolution laparoscopic confocal objective lens that provides cellular structural information equivalent to that provided by pathological biopsies in real time. With a field-of-view diameter of approximately 540 μ m and a lateral resolution of 1.95 μ m, which are sufficient for distinguishing cells, the system is both handheld and compatible with conventional laparoscopic trocar pins. Through ex vivo/in situ imaging experiments on various organs, including rat livers, kidneys, and spleens, the potential of this system in clinical applications is demonstrated.